EFL Teachers’ Views on English Assessment in 2013 Curriculum - Sari, Yulnada; Eriani, Efit; Pratolo, Bambang Widi (Universitas Cokroaminoto Palopo, 2020)
Teaching English as a foreign language in Indonesia faces several challenges not only from the teachers, students, facilities, teaching and learning process, but also how to assess the students. This present study purposed to investigate the English teachers’ views in conducting English assessments accordance in with 2013 curriculum. This study is a qualitative. The subject of this study is junior high school English teacher in Yogyakarta, Indonesia. The research data were collected through in-depth interview and observation. The results of the study suggested that before teaching, the teachers have prepared the lesson plans which included the rubric of the assessments in 2013 curriculum. English assessments that were used by the teachers were product, skill or knowledge assessment and attitude assessment. In product assessment, there were project and portfolio assessments, while skill or knowledge assessment consisted of writing, speaking, reading, and listening assessments. Thus, most of the teachers agreed with English assessment in 2013 curriculum because attitude assessment is separated from product, skill, and knowledge assessments. This study also revealed that the teachers encountered some problems in conducting the assessments dealing with student’s low motivation, lack of vocabulary, large amount of the student in the class, and shortage of teaching duration.